2005
DOI: 10.1007/s11103-005-2619-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in planta Interaction Evidence between Nicotiana tabacum Thaumatin-Like Protein 1 (TLP1) and Cucumber mosaic virus Proteins

Abstract: Using a yeast two-hybrid system, we identified a plant cellular factor that interacts with the proteins of the Cucumber mosaic virus (CMV). Initially 14 candidate genes were isolated from Nicotiana tabacum, using a full-length CMV 1a gene as bait. Among the candidate genes, two were encoding thaumatin-like proteins (TLP), and were designated as Nicotiana tabacum thaumatin-like protein 1 (NtTLP1). Consistent with this observation, recombinant GST-NtTLP1 protein, which was expressed and purified in E. coli, boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In fact, it was observed that the expression of CaAlaAT1 gene, which encodes a putative alanine aminotransferase, was dramatically induced in hot pepper plants (Capsicum annuum L. cv. Bugang) during the incompatible interaction with TMV [20]. However, we observed a downregulation of alanine aminotransferase in this study, which indicated that the defense response is more complex than a simple upregulation or downregulation of all potential defense proteins.…”
Section: Resultsmentioning
confidence: 46%
“…In fact, it was observed that the expression of CaAlaAT1 gene, which encodes a putative alanine aminotransferase, was dramatically induced in hot pepper plants (Capsicum annuum L. cv. Bugang) during the incompatible interaction with TMV [20]. However, we observed a downregulation of alanine aminotransferase in this study, which indicated that the defense response is more complex than a simple upregulation or downregulation of all potential defense proteins.…”
Section: Resultsmentioning
confidence: 46%
“…Thus, proteins involved in chromosome maintenance, motor and kinesin activities, hydrolases or cyclin-like proteins were among those upregulated; glutaredoxin-like proteins and cytochrome P450 were downregulated. Interpro allowed detection of proteins with other domains that might be related to defense response such as thaumatins [66], lipases [67] or proteins with leucine-rich repeats (Figure 4). …”
Section: Resultsmentioning
confidence: 99%
“…There are several examples suggesting that TLPs can interact with a variety of ligands and proteins including actin [57], cytokinin [58] and viral proteins [59]. The reason behind their involvement in various functions can be understood based on their ability to adopt functional diversification despite their conserved nature.…”
Section: Discussionmentioning
confidence: 99%